2006
DOI: 10.1093/brain/awl301
|View full text |Cite
|
Sign up to set email alerts
|

Startling facts about emotion in Parkinson's disease: blunted reactivity to aversive stimuli

Abstract: The amygdala is closely linked to basal ganglia circuitry and plays a key role in danger detection and fear-potentiated startle. Based on recent findings of amygdalar abnormalities in Parkinson's disease, we hypothesized that non-demented patients with this illness would show blunted reactivity during aversive/unpleasant events, as indexed by diminished emotional modulation of the startle eyeblink response. To test this hypothesis, 23 idiopathic patients with Parkinson's disease and 17 controls viewed standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 56 publications
9
100
0
Order By: Relevance
“…Thy1-aSyn mice show an agedependent deficit in this task, as well as in fear conditioning, likely to be due to the expression of a-synuclein aggregates in the amygdala (Freichel et al 2007), a brain area known to mediate emotional processes. These data are in line with the presence of Lewy bodies and Lewy neurite deposits in the amygdala of PD patients (Braak et al 1994), as well as the selective impairment in the recognition of facial emotion (Clark et al 2008) and blunted reactivity during aversive/unpleasant events observed in these patients (Bowers et al 2006).…”
Section: -Ohda-and Mptp-based Rodent Modelssupporting
confidence: 80%
“…Thy1-aSyn mice show an agedependent deficit in this task, as well as in fear conditioning, likely to be due to the expression of a-synuclein aggregates in the amygdala (Freichel et al 2007), a brain area known to mediate emotional processes. These data are in line with the presence of Lewy bodies and Lewy neurite deposits in the amygdala of PD patients (Braak et al 1994), as well as the selective impairment in the recognition of facial emotion (Clark et al 2008) and blunted reactivity during aversive/unpleasant events observed in these patients (Bowers et al 2006).…”
Section: -Ohda-and Mptp-based Rodent Modelssupporting
confidence: 80%
“…In nondemented PD patients, these alterations have been mainly associated with the concurrent progression of executive dysfunction resulting from progressive dopaminergic denervation along the frontalsubcortical circuitry and/or from pharmacological treatment (Starkstein et al, 1992;Aarsland et al, 1999;Isella et al, 2002;Pluck and Brown, 2002). However, recent research in the field of apathy as a syndrome has shown impaired emotion and reward processing in the absence of deficits of higher cognition (Bowers et al, 2006;Rowe et al, 2008;Martínez-Corral et al, 2010;Lawrence et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PD is also associated with abnormal autonomic (Bowers et al, 2006;Dietz, Bradley, Okun, & Bowers, 2011) and emotional responses (Ariatti, Benuzzi, & Nichelli, 2008) that may have affected our pattern of SCRs. Interestingly, we found that PD patients responded differently to correctly performed pairs compared to incorrectly performed pairs, but responded similarly to correctly performed rewarded and unrewarded pairs.…”
Section: Parkinson's Disease and Learningmentioning
confidence: 99%